GAMBARAN PENGETAHUAN IBU TENTANG TOILET TRAINING PADA ANAK USIA 18-36 BULAN DI YOGYAKARTA - Novi Istanti (Mikki: Majalah Ilmu Keperawatan dan Kesehatan Indonesia, 2019)
Background : Children under five years are children under 5 years of age, including toddlers, children aged 1-3 years. In balita, especially toddlers, one of the most important child development tasks is toilet training that if not given according to age will have an impact, namely the UTI, bedwetting and encopresis (Faecal incontinence), social problems, emotional problems, feeling different from other children, a sense of alienation and disability in children, low self-esteem, anxiety, symptoms of depression. The success of toilet training is influenced by various things, one of which is the readiness of parents, especially mothers, the readiness of mothers.Objective: Knowing the description of mothers' knowledge about toilet training in children aged 18-36 months in Yogyakarta. Method: This research uses descriptive method with a simple research design. The sample in this study were mothers who had children aged 18-36 months with a total of 34 respondents. Sampling using purposive sampling. The instrument used was a questionnaire. Data analysis uses percentages.Results: The results of this study note that 27 respondents (79.4%) included in the good knowledge category and 7 respondents (20.6%) in the sufficient knowledge category.